Nyctalus noctula ... - Honacki, James H.; Kinman, Kenneth E.; Koeppl, James W. (Zenodo, 1982)
Nyctalus noctula (Schreber, 1774). Saugethiere, 1:166. TYPE LOCALITY: France. DISTRIBUTION: Europe to Urals and Caucasus; Morocco; S.E. Asia Minor to Israel; W. Turkestan to S.W. Siberia, Himalayas, and China, south to Malaya; Taiwan; Honshu (Japan). COMMENT: Includes furvus and velutinus; see Corbet, 1978:55. ISIS NUMBER: 5301405014015006001. ... : Published as part of James H. Honacki, Kenneth E. Kinman & James W. Koeppl, 1982, Order Chiroptera, pp. 111-215 in Mammal Species of the World (1 st Edition), Lawrence, Kansas, USA :Alien Press, Inc. & The Association of Systematics Collections on page 193, DOI: 10.5281/zenodo.7352990 ...